2020
DOI: 10.1002/adfm.201910620
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Crystallized Multifunctional 2D Perovskite for Efficient and Stable Perovskite Solar Cells

Abstract: Recently, perovskite solar cells (PSC) with high power-conversion efficiency (PCE) and long-term stability have been achieved by employing 2D perovskite layers on 3D perovskite light absorbers. However, in-depth studies on the material and the interface between the two perovskite layers are still required to understand the role of the 2D perovskite in PSCs. Self-crystallization of 2D perovskite is successfully induced by deposition of benzyl ammonium iodide (BnAI) on top of a 3D perovskite light absorber. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 35 publications
3
52
0
Order By: Relevance
“…[30] Generally, the PSCs are optimized by compositional engineering of the absorber materials, optimizing the morphology, crystallinity, and grain size of a multicrystaline layer. [23][24][25][31][32][33] Other strategies like the incorporation of additives, [23,34] solvent engineering, [34,35] intermediate phase optimization, [36] mixed 2D and 3D systems, [37] or interface engineering [21] are often utilized to boost the performance toward either higher efficiency or stability. However, the surface underneath the perovskite layer also plays a vital role, as it dictates the film morphology and coverage.…”
Section: Introductionmentioning
confidence: 99%
“…[30] Generally, the PSCs are optimized by compositional engineering of the absorber materials, optimizing the morphology, crystallinity, and grain size of a multicrystaline layer. [23][24][25][31][32][33] Other strategies like the incorporation of additives, [23,34] solvent engineering, [34,35] intermediate phase optimization, [36] mixed 2D and 3D systems, [37] or interface engineering [21] are often utilized to boost the performance toward either higher efficiency or stability. However, the surface underneath the perovskite layer also plays a vital role, as it dictates the film morphology and coverage.…”
Section: Introductionmentioning
confidence: 99%
“…[ 134 ] Moreover, utilizing the randomly oriented crystalline structure of 2D PVSKs to facilitate hole transfer between 3D PVSK light absorber and HTL, the PCE improved from 19.75% to 20.79%. [ 135 ] Nowadays, phase‐pure 2D layered PVSK solar cells achieve a power conversion efficiency of 16.25% and after keeping them in 65 ± 10% humidity for 4680 h, under operation at 85 °C for 558 h, or continuous light illumination for 1100 h, the cells show <10% degradation. [ 87 ] The extraordinary stability of 2D PVSK provides extensive applications in many fields.…”
Section: Applicationmentioning
confidence: 99%
“…3 f displays the current density–voltage ( J – V ) properties, where it is observed that there is no current density ( J sc ) in the device under dark conditions [ 68 ]. The application of multi-functional 2D perovskites (M2P) with the hole transporting material (HTM) along with 2,2′,7,7′-tetrakis-( N , N -di-p-methoxyphenyl-amine)-9,9′-spirobifluorene (spiro-OMeTAD) light absorber increases both the effectiveness and the stability since M2P triggers faster hole transport and provides a passivation effect due to its randomly oriented crystal structure [ 69 ]. It is clear from Fig.…”
Section: Mechanisms and Performance Of 2d Nanomaterial-based Energy Scavenging Devicesmentioning
confidence: 99%
“…In addition, in the stage of spiro-OMeTAD on the basis of M2P requirements under the reverse and forward scan of the device, the stability of the perovskite solar cell improves by maintaining a maximum power point tracking to 80%, compared to 64%, in the case of applying M2P which is shown in Fig. 3 i [ 69 ]. The highest efficiency from a perovskite solar cell to date is 25.2% [ 70 ].…”
Section: Mechanisms and Performance Of 2d Nanomaterial-based Energy Scavenging Devicesmentioning
confidence: 99%